Reducing the corrosion rate of magnesium via microalloying additions of group 14 and 15 elements. (10th January 2018) - Liu, R.L.; Scully, J.R.; Williams, G.; Birbilis, N.
Abstract: A characteristic of magnesium (Mg) dissolution is that dissolution is accompanied by a concomitant increase in the hydrogen evolution reaction (HER), a phenomenon known as cathodic activation. When magnesium undergoes free corrosion or forced dissolution in response to anodic polarisation, cathodic activation is manifest, which allows magnesium dissolution to readily proceed. However, recent work revealed that alloying magnesium with micro additions of arsenic, As (a group 15 element) was capable of retarding cathodic activation, resulting in a significant reduction in the corrosion rate of Mg-As alloys. As such, in the pursuit of elements with similar chemical and electrochemical properties to arsenic, but with less toxicity, a number of group 14 and 15 elements were alloyed with magnesium and reported herein. Based on the binary alloying additions studied herein, it was revealed that Bi, Ge, Pb, Sb and Sn, demonstrated suppression of cathodic activation of Mg following anodic polarisation (about one order of magnitude lower based on the cyclic galvanostatic-potentiostatic testing), in addition to lower free corrosion rates (about one order of magnitude based on the mass loss and hydrogen evolution testing). Employing a number of corrosion rate assessments, including online atomic emission spectroelectrochemistry, it was shown that reduction in Mg corrosion rates – historically considered difficult to achieve – can be robustly demonstrated. The present work has implications for the development of more corrosion resistant Mg alloys, Mg anodes for cathodic protection, or for the use of Mg as a primary battery electrode.